PENGARUH KEPEMIPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN KOPERASI PRIMER KEPOLISIAN KOTA PADANG - Budi Yanti (Ensiklopedia of Journal, 2022)
The purpose of this study was to determine the influence of leadership and organizational culture on the performance of PRIMKOPPOL RESTA Padang Cooperative employees, either partially or simultaneously. The population and sample in this study were 36 employees of PRIMKOPPOL RESTA Padang Cooperative. The sampling technique in this study was the total sampling of the multiple linear regression equation model for the influence of leadership and organizational culture on performance as follows: Y = 4.814 + 0.080 X1 + 0.464 X2 + e The results of the multiple linear regression analysis obtained t test results, it was found that leadership has no significant effect on performance and organizational culture has a significant effect on performance. The results of the F test obtained that the leadership and organizational culture variables together have a significant effect on the performance variable. The results of the coefficient of determination test obtained the value of Adjusted R Square = 0.542 which means that about 54.2% of the leadership variable (X1) and organizational culture (X2) affect the performance variable. While the remaining 45.8% is influenced by other variables not examined in this study such as: motivation, career development, incentives and others.Keywords: Leadership, Organizational Culture, and Performance.